Influence of Soil Probiotic on Water Quality and Soil Quality Maintenance and Growth of Freshwater Fish Pangasius hypophthalmus - Bazar, Kiran Kumar; Pemmineti, Naga Jyothi; Mohammad, Subhan Ali (New Visions in Biological Science Vol. 8, 2022)
In recent decades, various procedures have been introduced to improve the conditions of the cultural ponds' conditions in aquaculture. Numerous biological products, including live bacterial inocula, preparation of enzymes, extracts of plant products, and many others, are being promoted to induce water and soil quality conditioners in aquaculture ponds. However, several studies have shown no significant effect of bacterial inoculums, and also the treatment with enzymatic preparation led to an enhancement of microbial mineralization of organic matter, but no effective net production of fish was observed. Probiotics have recently been applied to aquaculture. Probiotics are the live cells or a substrate that induce its benefits by stimulating growth, digestion, and active immune response. Probiotics can also improve water and soil quality. The use of probiotics is increasingly viewed as an alternative source of antibiotic treatment, which controls pathogens through various mechanisms. The current study summarizes the role of commercial probiotic ‘Super-PS’ on water quality and soil quality maintenance during the culture of freshwater fish Pangasius hypophthalmus fingerlings.